REVIEW OF OCCURRENCE OF MYCOTOXINS IN SERBIAN FOOD ITEMS IN THE PERIOD FROM 2005 TO 2022 - Živančev, Jelena; Antić, Igor; Buljovčić, Maja; Bulut, Sandra; Kocić-Tanackov, Sunčica (Food and Feed Research, 2022)
This paper aimed to review the publications on mycotoxins’ presence in cereals and foodstuffs originated from the Serbian market covering the period from 2005 to 2022. The review covers all the important steps in mycotoxins analysis including sampling, sample preparation, instrumental analysis, and concentration ranges in which the mycotoxins were found. Also, the results were interpreted from the European Union regulation point of view. The review emphasizes the importance of multi-mycotoxins analysis for determining the simultaneous presence of mycotoxins that can negatively affect the Serbian human population. The most frequently used instrumental technique in the mycotoxin analysis of Serbian products was the Enzyme-Linked Immunosorbent Assay followed by the Ultra-High Performance Liquid Chromatography coupled with triple quadrupole mass spectrometry. Most of the studies undertaken in Serbia until now investigated a few groups of matrices such as wheat, maize, milk, and dairy products. Only a few studies involved specific matrices such as nuts, dried fruits, biscuits, cookies, and spices. The review showed that contamination of milk and dairy products with aflatoxin M1 (AFM1), occurred at the very beginning of 2013, was the major health issue related to the population health. The contamination of milk and dairy products with the AFM1 was a consequence of maize contamination with aflatoxins which occurred in the year 2012, characterized by drought conditions. The studies dealing with the analysis of masked and emerging mycotoxins are rare and more attention should be paid to monitoring the presence of these types of mycotoxins in foodstuffs from Serbia.